Konsep Design Thinking pada Lembaga Bimbingan Belajar Smartnesia Educa - Ahmad Hadi Fauzi; Iwan Sukoco (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2019)
Design thinking has become one of the model approaches that can be carried out by a business entity. The design concept approach model is widely chosen because it has several stages and thought lines that are systematic, mutually sustainable, understanable and applicable. Therefore, this study aimed to determine the use of design thinking approach models in business entities, which are the research locus, namely in Smartnesia Educa. This research used a descriptive analysis method using a qualitative approach. The data collected was secondary and primary data in the form of interviews and supporting documents in Smartnesia Educa. The results of this study indicated that Smartnesia Educa had applied the design thinking in its operational business processes to become heterogeneous tutoring and could be accepted by all levels of economic and social markets.